Circulatory CNP Rescues Craniofacial Hypoplasia in Achondroplasia. (December 2017) - Yamanaka, S.; Nakao, Kazumasa; Koyama, N.; Isobe, Y.; Ueda, Y.; Kanai, Y.; Kondo, E.; Fujii, T.; Miura, M.; Yasoda, A.; Nakao, Kazuwa; Bessho, K.
Achondroplasia is the most common genetic form of human dwarfism, characterized by midfacial hypoplasia resulting in occlusal abnormality and foramen magnum stenosis, leading to serious neurologic complications and hydrocephalus. Currently, surgery is the only way to manage jaw deformity, neurologic complications, and hydrocephalus in patients with achondroplasia. We previously showed that C-type natriuretic peptide (CNP) is a potent stimulator of endochondral bone growth of long bones and vertebrae and is also a potent stimulator in the craniofacial region, which is crucial for midfacial skeletogenesis. In this study, we analyzed craniofacial morphology in a mouse model of achondroplasia, in which fibroblast growth factor receptor 3 (FGFR3) is specifically activated in cartilage ( Fgfr3 ach mice), and investigated the mechanisms of jaw deformities caused by this mutation. Furthermore, we analyzed the effect of CNP on the maxillofacial area in these animals. Fgfr3 ach mice exhibited midfacial hypoplasia, especially in the sagittal direction, caused by impaired endochondral ossification in craniofacial cartilage and by premature closure of the spheno-occipital synchondrosis, an important growth center in craniomaxillofacial skeletogenesis. We crossed Fgfr3 ach mice with transgenic mice in which CNP is expressed in the liver under the control of the human serum amyloid-P component promoter, resulting in elevated levels of circulatory CNP ( Fgfr3 ach /SAP-Nppc-Tg mice). In the progeny, midfacial hypoplasia in the sagittal direction observed in Fgfr3 ach mice was improved significantly by restoring the thickness of synchondrosis and promoting proliferation of chondrocytes in the craniofacial cartilage. In addition, the foramen magnum stenosis observed in Fgfr3 ach mice was significantly ameliorated in Fgfr3 ach /SAP-Nppc-Tg mice due to enhanced endochondral bone growth of the anterior intraoccipital synchondrosis. These results clearly demonstrate the therapeutic potential of CNP for treatment of midfacial hypoplasia and foramen magnum stenosis in achondroplasia.